Eco-Innovations In Urban Development: Bridging Civil Engineering And Environmental Sustainability - Vierdan Roweney Marek Janshevaski (CV. SINAR HOWUHOWU, 2025)
Urban development faces increasing challenges due to rapid population growth, environmental degradation, and the urgent need for sustainable infrastructure. This study explores the role of eco-innovations in bridging civil engineering and environmental sustainability through the integration of green technologies, sustainable materials, and smart urban systems. The research highlights how eco-innovative approaches—such as the use of renewable resources, life-cycle assessments, and digital tools like BIM and IoT—can reduce carbon footprints, enhance resource efficiency, and promote urban resilience. The findings indicate that sustainable engineering practices not only improve environmental performance but also align with global sustainability goals such as SDG 9 and SDG 11. The paper concludes that eco-innovations are essential to shaping future cities that are technologically advanced, environmentally balanced, and socially inclusive.